Addressing needs of seniors - Chee, Kwan Foong*; Long, Chiau Ming * (Star Media Group Berhad, 2023)
The International Day for Older Persons is celebrated on Oct 1 annually; this year, its theme is "Fulfilling the Promises of the Universal Declaration of Human Rights for Older Persons: Across Generation". It serves as a reminder and a call to action, emphasising the rights of senior people and the importance of intergenerational solidarity. Such a message aligns seamlessly with the broader vision of the United Nations Sustainable Goals (SDGS) that envision an inclusive, equitable, and sustainable future for everyone. (The SDGS are 17 interlinked objectives designed to serve as a "shared blue-print for peace and prosperity for people and the planet".)